Spectral beam splitting retrofit for hybrid PV/T using existing parabolic trough power plants for enhanced power output. (15th May 2020) - Wingert, Rhetta; O'Hern, Hannah; Orosz, Matthew; Harikumar, Parameswar; Roberts, Kenneth; Otanicar, Todd
Graphical abstract: Highlights: On-sun testing of beam splitting silicon PV retrofit to CSP using RP-3 mirrors. Modeling and experiments confirmed concentration ratio on PV receiver >20. Measured PV efficiency on average of 12% based on measure flux to modules. Improvements in tracking and PV module quality would yield significant improvements. Abstract: Conversion of sunlight into electricity is the fastest growing commercial means of deploying renewable energy at utility scale. The two primary methods for conversion are photovoltaics and concentrating solar thermal power. The complimentary advantages of these two methods motivates interest in hybridizing the two. Here, a spectral beam splitting approach is designed and tested for application as a retrofit in existing parabolic trough concentrating solar power facilities, the first large scale test using such an approach with low-cost silicon photovoltaic cells. Such an approach leverages the existing capital cost of the plant with the potential to boost plant output. The novel on-sun testing here focused on the electrical performance of a silicon photovoltaic module integrated into the most common parabolic trough geometry with a net aperture area of 1.7 m 2 . The spectral beam splitter has a solar weighted reflectance of 71.2%, and delivered an average flux to the cells of 17, 828 W/m 2 representing a concentration ratio of 25×, within 10% of the prediction of the optical ray tracing model. The two photovoltaic modules achieved an average efficiency - based upon measured irradiance delivered to the cells - of 12.4% (or 3% if normalized to the total aperture of the area of the mirror). A corresponding decrease in thermal performance was observed when the retrofit was added. Overall the design is capable of providing a path to retrofit existing parabolic trough powerplants to provide a 13% increase in power output using commercially available photovoltaic technology.